The Efforts to improve Children's Expressive Language Ability through Picture Book Media (Big Book) - Oktaviana Wulandari; Retno Firdiyanti; Rahmita Laily (Jurnal Perempuan dan Anak, 2022)
The golden age or period for early childhood (0-6 years) is a period where children experience very rapid growth and development, which then at the age of 4-6 years is a period where they take formal education such as Kindergarten. This period is a good time to develop language skills, physical, emotional, social, discipline and all the abilities of the child. In addition, family also plays an important role in the development of the children’s potential and growth. One of the important aspects in the growth and development of children is language skills, as the language is a means of communication with parents, teachers, and peers who are their present social environment. Children at this age cannot be separated from their parents or family as the children initially learn language from adult examples. At an early age, problems often occur because sometimes children cannot speak clearly and firmly which is caused by the slow development of children in language due to the lack of stimulus provided. Therefore, this study aims to improve expressive language skills of early childhood through the media of the Picture Book (Big Book).